2013
DOI: 10.4236/abcr.2013.24022
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Trastuzumab (Herceptin<sup>®</sup>): A UK Time and Motion Study in Comparison with Intravenous Formulation for the Treatment of Patients with HER2-Positive Early Breast Cancer

Abstract: Aim: Firstly, to quantify active healthcare professional (HCP) time and costs associated with subcutaneous (SC) administration of trastuzumab (Herceptin ® ) compared with the standard intravenous infusion (IV) in the treatment of patients with HER2-positive early breast cancer within the adjuvant PrefHer trial setting; secondly, to measure patient time in the care unit and patient infusion chair time for both routes of administration. Methods: A UK multi-centre prospective, observational Time and Motion study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
58
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 1 publication
5
58
3
Order By: Relevance
“…[5] A time-and-motion study within the PrefHer study demonstrated a mean time saving of 55-57 min of patient chair time and 13-17 min of active healthcare professional time per session with H SC compared with H IV, [6] and several countries have reported estimated increased hospital capacity and/or costsavings with H SC. [7][8][9][10][11][12][13][14][15][16][17] These data support a transition to SC delivery.…”
Section: Introductionmentioning
confidence: 82%
“…[5] A time-and-motion study within the PrefHer study demonstrated a mean time saving of 55-57 min of patient chair time and 13-17 min of active healthcare professional time per session with H SC compared with H IV, [6] and several countries have reported estimated increased hospital capacity and/or costsavings with H SC. [7][8][9][10][11][12][13][14][15][16][17] These data support a transition to SC delivery.…”
Section: Introductionmentioning
confidence: 82%
“…Our findings of the cost savings of SC are consistent with the results of similar CMA studies from Europe comparing IV and SC trastuzumab. CMAs conducted from the perspective of the England and Wales NHS (₤2013), the Greek health system (€1121), and the Scottish NHS (£3454) have all reported cost savings over 1 year of treatment with SC trastuzumab [21] [23] [25]. In addition, an analysis by Samanta et al estimated cost savings of £271,000 and reduction of pharmacists and nurses workload by 5492 hours from switching a cohort of 200 breast cancer patients from IV to SC trastuzumab in the English NHS [22].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned, we relied on estimates and opinions of the study investigators to estimate data inputs. Although we had involved four study sites and averaged the time and resource use to limit bias, since the method was based on opinion and recall rather than direct measurement of time expended in each activity as was performed in the study by Burcombe, there could still be potential information bias in the estimation [21]. However, the estimated nurses time for IV drug administration in this study (20 and 13.3 minutes for loading and subsequent doses) was within the range of those reported in other studies which ranged from 2 minutes in Denmark and Spain to 35 minutes in the UK per IV administration, and up to 60 minutes for an IV loading dose in the National University Hospital of Iceland [21] [24] [36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations